2011
DOI: 10.3810/pgm.2011.09.2467
|View full text |Cite
|
Sign up to set email alerts
|

Age of Depressed Patient does Not Affect Clinical Outcome in Collaborative Care Management

Abstract: Clinical response and remission for the treatment of depression has been shown to be improved utilizing collaborative care management (CCM). Prior studies have indicated that the presence of mental health comorbidities noted by self-rated screening tools at the intake for CCM are associated with worsening outcomes; few have examined directly the impact of age on clinical response and remission. The hypothesis was that when controlling for other mental health and demographic variables, the age of the patient at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, minor or sub‐threshold depression, depression and anxiety in residential care homes, suicidal ideation, alcohol abuse, behavioural symptoms in Alzheimer, and mental problems in specific patient groups …”
Section: Resultsmentioning
confidence: 99%
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, minor or sub‐threshold depression, depression and anxiety in residential care homes, suicidal ideation, alcohol abuse, behavioural symptoms in Alzheimer, and mental problems in specific patient groups …”
Section: Resultsmentioning
confidence: 99%
“…Covariates, selected based on prior work, 10,12,18 include age, sex, marital status, race, depression diagnosis, the initial PHQ-9 score, and the treatment variable of enrollment in CCM. Two Cox models were used, 1 with a dependent variable of remission and the other with a dependent variable of PDSs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were identified [31-35]; they were categorized by the population studied and the treatment required into pediatric, adult OTC, and adult prescription. Given the absence of data for the cost of pediatric non-prescription care, the base case assumes that adult and pediatric OTC annual costs are equivalent.…”
Section: Methodsmentioning
confidence: 99%